Understanding microplastics in aquatic ecosystems –A mini review - Soo, Chen Lin; Shahirah Sabana; Chen, Cheng Ann; Yii-Siang Hii (Universiti Malaysia Sabah, 2021)
Microplastic is defined as plastic debris with a size less than 5mm. It is characterized based on colour, shape, and polymer type. Microplastics have been discovered in a variety of aquatic environments, including freshwater, estuarine, and marine waters. The presence of microplastic in aquatic systems poses a threat not only to aquatic organisms, but to human consumers of food harvested from these environments. This paper reviews the key characteristics of microplastics, how they contaminate aquatic ecosystems, and their effects on aquatic organisms. Efforts have been made to highlight the knowledge gaps in these areas and measures that deserve attention for addressing the problem.